Diffusion of electronic commerce (B2C) in Oman through education sector -an analysis based on E.M. Rogers' theory of diffusion of innovations (DoI) 1995 - Ali, Basharat; Baluch, Nazim Hussain; Mohamed Udin, Zulkifli (2014)
Notwithstanding Sultanate of Oman is recently entitled as one of the fastest growing nations over the last 40 years among 135 states in the world and is grouped as the most developed and stable country in the region by the United Nations Development Program me, it ranks low in the list of electronic commerce (EC) practicing countries worldwide.Indeed, it is locals' attitude towards EC that has been resulting in country's lower position in the list states pursuing EC and not technological infrastructure.Addressing important factors effecting persuasion of business-to-consumer (B2C) e-commerce in Oman, this paper aims to uphold a thorough analysis by using E.M. Rogers's theory of diffusion of innovations (DoI) and come up with a proposed framework and valuable suggestions those will help diffusing EC within the Sultanate.In this regard, it is recommended that intellectuals including; academicians, scholars and students can play a vital role by conducting interpersonal communication across the community.